Ethylene signaling regulates natural variation in the abundance of antifungal acetylated diferuloylsucroses and Fusarium graminearum resistance in maize seedling roots. Issue 4 (2nd November 2018) - Zhou, Shaoqun; Zhang, Ying K.; Kremling, Karl A.; Ding, Yezhang; Bennett, John S.; Bae, Justin S.; Kim, Dean K.; Ackerman, Hayley H.; Kolomiets, Michael V.; Schmelz, Eric A.; Schroeder, Frank C.; Buckler, Edward S.; et al.
Summary: The production and regulation of defensive specialized metabolites play a central role in pathogen resistance in maize ( Zea mays ) and other plants. Therefore, identification of genes involved in plant specialized metabolism can contribute to improved disease resistance. We used comparative metabolomics to identify previously unknown antifungal metabolites in maize seedling roots, and investigated the genetic and physiological mechanisms underlying their natural variation using quantitative trait locus mapping and comparative transcriptomics approaches. Two maize metabolites, smilaside A (3, 6‐diferuloyl‐3′, 6′‐diacetylsucrose) and smiglaside C (3, 6‐diferuloyl‐2′, 3′, 6′‐triacetylsucrose), were identified that could contribute to maize resistance against Fusarium graminearum and other fungal pathogens. Elevated expression of an ethylene signaling gene, ETHYLENE INSENSITIVE 2 ( ZmEIN2 ), co‐segregated with a decreased smilaside A : smiglaside C ratio. Pharmacological and genetic manipulation of ethylene availability and sensitivity in vivo indicated that, whereas ethylene was required for the production of both metabolites, the smilaside A : smiglaside C ratio was negatively regulated by ethylene sensitivity. This ratio, rather than the absolute abundance of these two metabolites, was important for maize seedling root defense against F. graminearum . Ethylene signaling regulates the relative abundance of the two F. graminearum ‐resistance‐related metabolites and affects resistance against F. graminearum in maize seedling roots.